Merunut Pemahaman Taksonomi Bloom: Suatu Kontemplasi Filosofis - Tulasi, Dominikus (Bina Nusantara University, 2010)
This article would like to share the use of Bloom's taxonomy as a cognitive framework for teaching-learning process to undertake the way student-centered learning. Related to the curriculum based competence in excellent education, the abstract cognitive in applying Bloom’s taxonomy is so called scaffolding. We know the taxonomy Bloom is a six-level classification system that uses observed student behavior to infer and absorb the level of cognitive achievement domain. This article surveys thinking within general education and management education, which uses and draws on Bloom's taxonomy, and then describes suggested uses of the taxonomy. The empirical evaluation of its effect on student achievement follows, as do thoughts about ways colleagues might use this tool to empower and motivate students as self-responsible learners in the classroom. The objective is to promote higher order thinking in college students, we understood an effort to learn how to assess critical-thinking skills in an introductory course. It means, we develop a process by which questions are prepared with both content and critical-thinking skills in mind.